Having it both ways: learning communication skills in face-to-face and online environments - Eklund, Marja; Isotalus, Pekka (Frontiers in Education, 2024)
In early 2020, the COVID-19 pandemic forced educators to transition to online teaching almost overnight. This paper focuses on students' perceptions of communication skills in a practice course in the spring of 2020. The beginning of the course was held face-to-face and conducted online at the end. We sought information regarding students' experiences of online course in a skill-based course.Relying on knowledge about online communication, we selected three areas to focus on in online course. First, feedback is essential in the process of learning communication skills and is included in the course learning objectives. Second involves eliciting conversations in an online environment. The third area is the connection between the audience and the speaker in public speaking. Our goal was to develop the course according to student's perceptions. At the end of the course, 26 students answered open-ended questions about the two forms of implementation. Using thematic analysis, five different themes were constructed: 1) positive perceptions of the course, 2) neutral perceptions of online course, 3) perceptions of the challenges in online course, 4) perceptions of public speaking, and 5) perceptions of feedback. During the course, the students learned much-appreciated computermediated communication. They believed that the good learning results were due to careful organization and connection to other students. While uncommon, few students perceived online course as neither good nor bad, just neutral. Nevertheless, online course was not without challenges; students identified several problems concerning, for example, conversations and nonverbal communication. Furthermore, students considered feedback to be successful; however, online public speaking was perceived as different from speaking to a physical audience. The results of this study indicate that in a skill-based course, the online format can be just as effective as the face-to-face format. However, especially because public speaking was regarded as different and participants appreciated practicing communication in the online setting, we suggest that students should have the opportunity to practice communication skills both online and face-to-face. Additionally, although conversations received special attention, it caused the most significant challenges in the online